Implementation of Strengthening State Science Knowledge Using Camp Study Methods on PPKn Students Of PGRI Banyuwangi University - Andika Ronggo Gumuruh; Agus Mursidi; Tofan Priananda Adinata; Eko Listiwikono (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2021)
Knowledge of state science is the basis for maintaining state institutions, so that research is carried out continuously and scientifically, as well as solving problems in students' knowledge of state science. The purpose of this service is to provide reinforcement to students about state science by presenting state science practitioners. Knowledge skills about state science and student attitudes towards the development of the country. This activity was attended by 25 PPkn students of PGRI Bnyuwangi University batch 2020. The method used was to present speakers of political practitioners and student activists in 1998 so that the level of student knowledge about state science and the role of students in the movement to build the nation could become the spirit of students in the reform era. In practice, students' knowledge of state science is increasing and it can be concluded that the role of students to maintain the institution is very important.